DAMPAK MEDIASI ORGANISATIONAL CITIZENSHIP BEHAVIOUR TERHADAP EMPLOYEE PERFORMANCE DENGAN ANTESEDEN CAREER JOURNEY, SELF-EFFICACY DAN QUALITY OF WORK LIFE PADA INSTANSI DIREKTORAT JENDERAL PAJAK - Lia Amsalia Amir; Anshar Daud; Hendrian Hendrian (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2023)
The purpose of this study was to examine the indirect effect of Organizational Citizenship Behavior (OCB) on employee performance by using the antecedents of Career Journey, Self Efficacy and Quality of Work Life. This study also examines the direct role of the variables Career Journey, Self Efficacy and Quality of Work Life on employee performance at the Directorate General of Taxes. This type of research is quantitative using a questionnaire research instrument to collect data. The sample for this research is all employees at the Directorate General of Taxes who are taken using probability sampling. The data analysis method used is Structural Equation Modeling Partial Least Square (SEM-PLS). The results showed that Career Journey, Self Efficacy, Quality of Work Life had a positive effect on Organizational Citizenship Behavior, then Career Journey, Quality of Work Life and OCB also had a positive effect on employee performance, but Self Efficacy had no significant effect on employee performance. In addition, Organizational Citizenship Behavior is also proven to be able to mediate the relationship between Career Journey, Self Efficacy and Quality of Work Life towards employee performance. The findings of this study contribute to the development of theories related to Organizational Citizenship Behavior and the importance of managing career paths, employee self-motivation and the quality of employee work life so that employees can provide maximum performance which will certainly support organizational performance.